PENERAPAN PEMBELAJARAN KONSTRUKTIVISME MENGGUNAKAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR GEOMETRI PESERTA DIDIK - Mirna, Mirna; Mukhaiyar, Mukhaiyar; Ananda, Azwar (JURNAL LEMMA, 2024)
The purpose of this study was to determine the development of geometry learning outcomes for class VIII SMP students through the application of constructivist learning using interactive multimedia. The research method used is Classroom Action Research. The subjects of this study were 32 junior high school students. Data collection tool in the form of learning tests. The data analysis technique used in this study is descriptive statistical analysis and graphical methods. The implementation of this research consisted of three cycles which identified more than 70 indicators of the success of students' attitudes and learning outcomes of geometry. The results obtained, the application of constructivism through interactive multimedia can improve student learning outcomes. However, this growth is still far from expectations. Only 15.625% of students feel their learning outcomes have increased and the rest are constant or variable. In the final test of this study, only 72.875% of students reached the set criteria.